REFLECTION OF OUR NATIONAL TRADITIONS IN THE ORAL CREATION (International Conference on Education, Psychology and Humanities, 2026)
The article discusses the ancient customs, traditions, values, family-household ceremonies of our people, as well as the “og‘iz iskash”, “atashtirib qoʻyish” and other ceremonies in the “Alpamish” epic.
Keywords: Epic, traditions, values, “Alpamish”, courtship, marriage, people, tradition.